Algal polysaccharides: Structure, preparation and applications in food packaging. (30th March 2023) - Thiviya, Punniamoorthy; Gamage, Ashoka; Liyanapathiranage, Anuradhi; Makehelwala, Madhubhashini; Dassanayake, R.S.; Manamperi, Asanga; Merah, Othmane; Mani, Sudhargar; Koduru, Janardhan Reddy; Madhujith, Terrence
Highlights: Summarized recent extraction process for agar & carrageenan, alginates and ulvan. Summing up the numerous uses for polysaccharides generated from macroalgae. Summarized the physicochemical and mechanical properties algal polysaccharides. Reviewed algal polysaccharide potential use in edible, active, and food packaging. Abstract: Algal polysaccharides have become more popular in the food and packaging industry because of their excellent physicochemical properties. Further, the use of biodegradable, biobased polymers as an alternative renewable source for developing environmentally friendly materials has emerged as a substitute for non-renewable plastic materials. In this regard, algal polysaccharide-based biopolymers are highly studied in the development of novel packaging materials with the improved barrier, mechanical, antioxidant, and antimicrobial properties. In this review, major algal polysaccharides, such as galactans (agar, carrageenan), alginates, and ulvan, are mainly considered and will give information about their structure, properties, and applications in the food packaging industry.